Joys of Christmas. Issue 1 (June 2019) - Jodha, Vijay S.
This photo essay captures some of the female entrepreneurs who operate from the footpaths of Connaught Place—New Delhi's oldest and toniest shopping district, around Christmas. Notwithstanding their unusual appearance, each woman embodies the many challenges common to labour in unorganized sector in India and the world.